A Robust and Efficient Numerical Method for RNA-Mediated Viral Dynamics - Reinharz, Vladimir; Churkin, Alexander; Dahari, Harel; Barash, Danny (Frontiers in Applied Mathematics and Statistics, 2017)
The multiscale model of hepatitis C virus (HCV) dynamics, which includes intracellular viral RNA (vRNA) replication, has been formulated in recent years in order to provide a new conceptual framework for understanding the mechanism of action of a variety of agents for the treatment of HCV. We present a robust and efficient numerical method that belongs to the family of adaptive stepsize methods and is implicit, a Rosenbrock type method that is highly suited to solve this problem. We provide a Graphical User Interface that applies this method and is useful for simulating viral dynamics during treatment with anti-HCV agents that act against HCV on the molecular level.